Barium titanate coated Ni particle material synthesized with assistance of spray drying technology and method of barium titanate coated Ni particle material

The spray drying technology coats the barium titanate layer on the surface of the nickel powder to form Ni@BaTiO3 spherical particles, which solves the problem of mismatch between the sintering shrinkage rate of the nickel powder and the ceramic dielectric layer and insufficient oxidation resistance, and achieves better sintering performance and oxidation resistance.

CN119634725AActive Publication Date: 2025-03-18DALIAN UNIV OF TECH

Patent Information

Application Number
CN202411836888.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-18
Estimated Expiration
2044-12-13

AI Technical Summary

Technical Problem

The shrinkage rate of nickel powder and ceramic dielectric layer in MLCC does not match during sintering, resulting in increased internal stress and defects such as cracks and stratification may occur. At the same time, the oxidation resistance of nickel powder is insufficient.

Method used

Through spray drying technology, metatitanic acid and barium hydroxide are mixed with nano and submicron-scale nickel powder to form barium titanate coated nickel powder and Ni@BaTiO3 spherical particles with core-shell structure, improving the oxidation resistance and sintering properties of nickel powder.

Benefits of technology

The sintering shrinkage matching between the nickel powder and the ceramic dielectric layer is improved, internal stress is reduced, cracks and layered defects are prevented, and the oxidation resistance and sintering performance of the nickel powder are significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119634725A_ABST
    Figure CN119634725A_ABST
Patent Text Reader

Abstract

The invention discloses a barium titanate coated Ni particle material synthesized under the assistance of a spray drying technology and a method thereof, and belongs to the technical field of metal powder material preparation. The method comprises the following steps: firstly, taking metatitanic acid and barium hydroxide as raw materials, and mixing the metatitanic acid and the barium hydroxide with nano and submicron Ni powder to prepare a mixed solution; secondly, synthesizing a Ni-based composite material intermediate by adopting a spray drying method; and finally, sintering in a tubular furnace to form the barium titanate coated Ni powder. The barium titanate coated Ni inner electrode material is Ni coated BaTiO3 spherical particles with a core-shell structure, the particles are of a core / shell microstructure, a shell layer is a barium titanate coating layer with the thickness of 10-15 nm, and the particle size of the particles is 100-150 nm. According to the method, required equipment can be scaled, components and microstructures are easy to regulate and control, and the method has high sphericity and dispersity, high compactness and good repeatability; the particle size and distribution can be changed by adjusting process parameters; meanwhile, good interface bonding with a ceramic dielectric layer is realized, and the key problems of mismatching of interlayer interface volume shrinkage, easy cracking and the like in the sintering process are relieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal powder material preparation, and relates to a spray drying technology-assisted synthesis of barium titanate-coated Ni particle material and a method thereof. The prepared metal powder has excellent oxidation resistance and sintering performance. Background Art

[0002] Multilayer ceramic capacitors (MLCCs) occupy an important position in electronic components, and one of their key technologies is the selection of internal electrode materials and performance optimization. From a historical perspective, precious metals (such as platinum and palladium) were initially used as internal electrode materials, mainly because they exhibit excellent oxidation resistance and stability at high temperatures. However, with the growing demand for low-cost, high-performance MLCC devices and the increase in the number of stacks, expensive precious metal materials have gradually been replaced by nickel (Ni), becoming a typical base metal electrode material. Nickel powder has the following advantages as an internal electrode material for MLCCs: low cost (more economical than precious metals); high electrical conductivity (ensuring excellent electrical conductivity of the electrode); low electrical mobility (reducing performance degradation during long-term use); good corrosion resistance and heat resistance (adaptable to a variety of working environments); and high sintering temperature (can form a stable structure when co-fired with ceramics). Therefore, nickel powder has become the most widely used internal electrode material in current MLCCs.

[0003] Nickel powder has obvious advantages in MLCC, but its practical application still faces many technical challenges: for example, nickel is easily oxidized to form nickel oxide (NiO) during high-temperature sintering, while ceramic dielectrics based on BaTiO3 are easily reduced to semiconductors when sintered in low oxygen partial pressure or reducing atmosphere; the sintering shrinkage rate of nickel inner electrode does not match that of ceramic dielectric. When the ceramic film and the inner electrode containing Ni powder are co-fired, the ceramic film cannot shrink together with the Ni film, and the Ni film is stretched in the plane direction. Voids are easily generated inside the electrode, which aggravates the discontinuity of the electrode and may lead to interlayer peeling or structural defects. In addition, the mutual diffusion and chemical reaction between nickel and ceramic dielectric during sintering will also affect the stability of the interface, thereby weakening the long-term reliability of the capacitor. At present, there are two main methods to improve the performance of metal nickel powder: one is to improve the microstructure of nickel powder, including crystallinity and particle size. Nickel powder with high crystallinity has good oxidation resistance, while nickel powder with small particle size can form dense and smooth nickel electrodes at lower sintering temperatures, which is suitable for the inner electrode slurry of MLCC. The second is to modify the surface of nickel powder. A common method is to form a coating layer on its surface, such as zirconium oxide (ZrO2), calcium carbonate (CaCO3), barium oxide (BaO), calcium zirconate (CaZrO3), strontium zirconate (SrZrO3), titanium dioxide (TiO2), silicon dioxide (SiO2), etc., to improve oxidation resistance and solve the problem of mismatch with the sintering shrinkage rate of ceramics.

[0004] Barium titanate (BaTiO3) is a lead-free piezoelectric ceramic material. Due to its excellent high dielectric constant, low loss characteristics, and excellent piezoelectric and ferroelectric properties, it is widely used in MLCC and positive temperature coefficient thermistors (PTC) and other fields, and is known as the "pillar of the electronic ceramic industry". Patent CN103508736A proposes a two-step method for surface modification of nickel powder, combining the two methods of atmospheric pressure coating hydrothermal crystallization and atmospheric pressure coating crystallization, and successfully coating the surface of nickel powder particles with a barium titanate layer, thereby effectively improving the oxidation resistance and sintering properties. However, the addition of excessive chemicals increases production costs and limits its large-scale application. In patent JP2004183027A, a chemical method is used to coat the surface of nickel powder with barium titanate ceramic dielectric material. Although the oxidation resistance and sintering properties are improved to a certain extent, the operation process is complicated and the coating effect is not good. In patent CN118847991A, a physical vapor phase preparation method for in-situ coating of nickel powder with barium titanate is introduced. This method realizes in-situ synthesis of barium titanate ceramic layer by thermal plasma co-evaporation of multi-component target materials, which significantly improves the shrinkage performance of nickel electrode. In this preparation process, there are shortcomings such as difficult composition control and high energy consumption.

[0005] In the preparation process of composite materials and core-shell particle materials, the synthesis method is crucial. Common synthesis methods such as chemical vapor deposition, sol-gel method and hydrothermal method all have certain limitations, such as complex operation and involving multiple chemicals, environmental pollution and other problems. Spray drying, as an efficient and multifunctional technology, shows great potential for industrial expansion and application. Initially, this technology was used in the pharmaceutical industry to produce pure APIs. It has attracted much attention due to its advantages such as simple operation, easy large-scale production, high yield and low environmental impact. Its application has rapidly expanded to cosmetics, textiles, electronic materials, microcapsules, controlled release particles, composite microparticles, nanoparticles and liposomes. Today, spray drying technology has developed into a process with high efficiency, simplified process, compact structure and excellent product quality. Patent CN 116675248 A uses wollastonite as a silicon source, controls the solid-liquid reaction rate by controlling temperature and acidity, and slowly generates silicon dioxide from wollastonite, which promotes heterogeneous nucleation on the surface of nano-titanium dioxide to form a uniform and continuous silicon dioxide coating layer, greatly improving the photostability and dispersibility of titanium dioxide. Patent CN109638273A discloses a coating method for preparing positive electrode materials for sodium ion batteries using spray drying. By precisely controlling process parameters such as air inlet temperature, feed rate, air flow rate and gas medium, the microstructure, particle distribution and performance of the powder can be effectively controlled. Spray drying technology has high production efficiency, excellent particle dispersion, and can ensure the uniformity of the coating layer thickness. Summary of the invention

[0006] The present invention is to solve the key technical problems such as the mismatch between the shrinkage rate of the inner electrode Ni powder and the ceramic medium and the poor oxidation resistance of the Ni powder during the co-sintering process of the MLCC metal inner electrode and the ceramic dielectric layer, and provides a preparation method and technology of BaTiO3 coated Ni powder with high sintering temperature, low shrinkage rate and strong oxidation resistance. The method uses metatitanic acid and barium hydroxide as the main raw materials, mixes with nano and submicron nickel powder to form a uniform solution, uses spray drying technology to obtain coated modified nickel powder, and then conducts a thermal reaction treatment in a N2 atmosphere to obtain Ni@BaTiO3 spherical particles with a core-shell structure. This coated nickel particle material is used as the inner electrode layer of the MLCC to improve the matching degree of the sintering shrinkage rate between the dielectric layer (BaTiO3), reduce internal stress to prevent the generation of defects such as cracks and delamination, and improve the continuity of the electrode and the qualified rate of the product.

[0007] To achieve the above purpose, the technical solution adopted by the present invention is:

[0008] A spray drying technology assisted synthesis of barium titanate coated Ni particle material and method thereof. The barium titanate coated Ni inner electrode material is a Ni@BaTiO3 spherical particle with a core-shell structure, which is a barium titanate coated modified Ni powder material obtained by coating Ni powder. The particles are a core / shell microstructure, the shell layer is a barium titanate coating layer with a thickness in the range of 10 to 15 nm, and the particle size is between 100 and 150 nm. The finished powder has good sphericity, crystallinity and purity.

[0009] The presence of the barium titanate coating layer improves the oxidation resistance and sintering performance of the powder, improves the continuity of the electrode, and thus improves the qualified rate and service life of the product.

[0010] The core / shell microstructure, particle size and distribution of the particles are regulated by controlling the ratio of barium hydroxide and metatitanic acid, the type and addition amount of the dispersant and parameters related to the spray drying process.

[0011] A spray drying technology-assisted synthesis of barium titanate-coated Ni particle material and method thereof. The method firstly uses metatitanic acid and barium hydroxide as raw materials, mixes with nano- and submicron Ni powders to prepare a mixed solution; secondly, a Ni-based composite material intermediate is synthesized by spray drying based on the obtained mixed solution; finally, barium titanate-coated Ni powder is formed after sintering in a tubular furnace (N2 atmosphere). The method comprises the following steps:

[0012] The first step is to pretreat the Ni powder raw material;

[0013] Ni powder is added into a dilute sodium carbonate solution, and ultrasonic cleaning is performed on the solution to obtain an alkaline solution containing Ni powder; the alkaline solution containing Ni powder after ultrasonic cleaning is cleaned with deionized water at room temperature to obtain Ni powder cleaned with deionized water; the Ni powder is nanometer or submicron or a mixed powder of nanometer and submicron.

[0014] The second step is to prepare the feed liquid;

[0015] At room temperature, the Ni powder and dispersant after the first step pretreatment are added to the solvent, dispersed by a homogenizer for 5 to 10 minutes, and then ultrasonically treated for 10 to 30 minutes to obtain a suspension A; at room temperature, barium hydroxide is dissolved in an aqueous solution, ultrasonically dispersed and vibrated for 10 to 30 minutes, and then titanic acid is added, dispersed by a homogenizer for 10 to 30 minutes, and then ultrasonically dispersed and vibrated for 10 to 30 minutes to obtain a suspension B; at room temperature, the suspension B is added to the suspension A, mechanically stirred for 6 to 12 hours, and fully mixed to obtain a suspension C for spray drying.

[0016] Furthermore, the solvent in the suspension A includes deionized water, ethanol, ethylene glycol and other organic solvents or their mixed solvents, preferably deionized water; the dispersant includes polyvinyl pyrrolidone (PVP), polyethylene glycol, citric acid, sodium citrate and the like or one or more mixtures thereof;

[0017] Furthermore, in the suspension A, the mass ratio of Ni powder to dispersant is 5:(1-3), and the concentration of Ni powder is 4 g / 1L.

[0018] Furthermore, in the suspension B, the molar ratio of titanic acid to barium hydroxide is 1:1 to 1:4.

[0019] Furthermore, the volume ratio of the suspension A to the suspension B is 10:1.

[0020] The third step is to prepare the Ni-based composite intermediate by spray drying;

[0021] A spray drying device is used to prepare a Ni-based composite intermediate using the suspension C prepared in the second step as the formal liquid material. The specific process steps are: setting the circulating air volume and air inlet temperature of the central fan of the spray drying device, the outlet pressure of the air compressor, the high-pressure gas flow rate, and the speed of the peristaltic pump. When the air inlet temperature display is the same as the set temperature display or the outlet temperature display exceeds 90°C, and it is determined that the spray drying device has reached various preset indicators and is operating normally and stably, the spray drying process of the formal liquid material (the suspension prepared in the first step) can be entered, and the Ni-based composite intermediate can be obtained after spray drying.

[0022] Step 4: preparing barium titanate coated Ni powder by heating under N2 atmosphere;

[0023] The powder collected after spray drying is placed in a tubular furnace, the tubular furnace is vacuumed, and heated and decomposed at 500-700°C for 4-6 hours. After the tubular furnace is cooled to room temperature, the final powder product is collected.

[0024] The specific working principle and innovation of the present invention are:

[0025] The pretreated nickel powder is mixed with barium hydroxide Ba(OH)2 and metatitanic acid TiO(OH)2 to prepare a composite material by spray drying technology. Subsequently, calcination and heating are carried out in a nitrogen atmosphere to obtain a capsule material of BaTiO3 coated nickel powder. The basic principle is as follows: the feed solution or suspension is pumped into the drying chamber through a nozzle. Compressed air is ejected from the air inlet pipe at a high speed, while the liquid material with a lower flow rate is ejected from the feed pipe, and there is a significant relative speed between the two. This relative motion generates friction and shear force between the gas and the liquid, causing the liquid to be pulled into a thin line and broken at the thin part of the thin line to form tiny droplets. Each droplet is wrapped with barium hydroxide and one or more metatitanic acid and nickel powder particles. The atomized droplets come into contact with the hot gas (usually air) in the drying chamber. During the process of passing through the drying chamber, energy and mass transfer occurs on the surface of the droplets, and the solvent is rapidly evaporated. Finally, the dried material is separated from the drying medium by a cyclone separator and collected in a collection device. The collected powder product is a composite material of barium hydroxide coated Ni and metatitanic acid. Then, it is heated and decomposed in a tube furnace (N2 atmosphere), and the reaction occurs: TiO(OH)2+Ba(OH)2=BaTiO3+2H2O. During this process, the barium hydroxide coated on the surface of the nickel powder reacts with metatitanic acid to generate barium titanate and water. After the water vapor evaporates, a barium titanate-coated nickel powder with a core-shell structure is formed. The spray drying parameter setting has a great influence on the powder coating effect. The feed injection speed directly affects the droplet size, movement trajectory and droplet movement speed. At the same time, the increase in the amount of liquid fed per unit time also means that more solvent needs to be vaporized in the same time. Usually, a lower solution feed rate can obtain better atomization effect and smaller droplet size. Drying is the stage of converting droplets into dry particles. At this stage, the higher the drying temperature, the faster the solvent loss on the droplet surface, which can not only lead to fewer undried particles attached to the wall of the drying chamber and increase the yield, but also affect the solute shrinkage rate and change the particle morphology. From this point of view, the higher the inlet temperature, the better. However, in practical applications, the drying temperature should still be controlled within a reasonable range due to reasons such as thermal stability of materials, energy consumption of equipment, and possible blockage of passages. The process parameters of spray drying have a significant effect on the coating effect of powders. The injection rate of the feed directly affects the size, trajectory, and movement speed of the droplets. At the same time, the increase in the amount of liquid fed per unit time means that more solvent needs to be evaporated in the same time. Generally, a lower solution feed rate can achieve better atomization effect and smaller droplet size. The drying process is a key stage in converting droplets into dry particles. At this stage, a higher drying temperature will accelerate the loss of solvent on the droplet surface, thereby reducing the undried particles attached to the wall of the drying chamber and increasing the yield. In addition, the drying temperature will also affect the rate of solute shrinkage, thereby changing the morphology of the particles. Therefore, theoretically, the inlet temperature should be as high as possible.However, in practical applications, the drying temperature still needs to be controlled within a reasonable range due to factors such as the thermal stability of the material, equipment energy consumption, and possible blockage of the channel.

[0026] The innovation of the present invention is to combine spray drying with chemical precipitation, and propose a novel low-cost, green and environmentally friendly method for preparing nano- and submicron Ni@BaTiO3 core-shell structure metal powders. By adjusting the process parameters of spray drying and the type of dispersant, the shortcomings of the single chemical precipitation method, such as the difficulty in controlling the coating thickness, the unsuitability for large-scale production and the poor powder dispersibility, are solved.

[0027] The beneficial effects of the present invention are:

[0028] (1) The present invention provides a process combining a traditional chemical method and a spray drying method for preparing nano-scale / submicron-scale metal powder coating materials. Compared with the traditional chemical method, the powder prepared by the method of the present invention has the following advantages: the required equipment can be scaled up, the raw materials are economical and environmentally friendly, the production cost is low, the composition and microstructure are easy to control, and it has high sphericity and dispersibility, high density, and good repeatability. By adjusting the process parameters, the particle size and its distribution can be changed.

[0029] (2) The dispersion of Ni powder is effectively improved, reducing agglomeration; it plays a role in protecting the metal Ni core, making it less prone to oxidation and improving its oxidation resistance; at the same time, it achieves a good interface bonding with the ceramic dielectric layer, thereby alleviating key problems such as volume shrinkage mismatch and easy cracking at the interlayer interface during the sintering process. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 It is the X-ray diffraction spectra of the pure Ni powder prepared in Comparative Example 1 and the barium titanate-coated Ni powder prepared in Examples 1-3.

[0031] Figure 2 The SEM image (a) and EDS spectrum of the barium titanate-coated Ni powder prepared in Example 2 show the element distribution of Ni (b), Ti (c), Ba (d), and O (e).

[0032] Figure 3 is the line scanning element corresponding curve of the barium titanate coated Ni powder prepared in Example 2; Figure 3 (a) is a line scan diagram of Example 1; Figure 3 (b) is the line scan element distribution diagram of Example 1.

[0033] Figure 4 is the SEM morphology of the barium titanate coated Ni powder prepared in Examples 1 to 4; Figure 4(a) is a SEM morphology of the barium titanate-coated Ni powder prepared in Example 1; Figure 4 (b) is the SEM morphology of the barium titanate-coated Ni powder prepared in Example 2; Figure 4 (c) is the SEM morphology of the barium titanate-coated Ni powder prepared in Example 3; Figure 4 (d) is the SEM morphology of the barium titanate-coated Ni powder prepared in Example 4.

[0034] Figure 5 It is the volume shrinkage rate of the barium titanate coated Ni powder prepared in Example 1 compared with the pure Ni powder prepared in Example 1.

[0035] Figure 6 It is the volume shrinkage rate of the barium titanate coated Ni powder prepared in Example 2 compared with the pure Ni powder prepared in Example 1.

[0036] Figure 7 It is the volume shrinkage rate of the barium titanate coated Ni powder prepared in Example 3 compared with the pure Ni powder prepared in Example 1.

[0037] Figure 8 It is the volume shrinkage rate of the pure Ni powder prepared in Example 1 and the barium titanate coated Ni powder prepared in Example 4.

[0038] The above contents of the present invention will be further described in detail below in conjunction with specific implementation modes, but the scope of the present invention is not limited to the following examples:

[0039] Comparative Example 1:

[0040] 1. Preparation process

[0041] Pure Ni powder without barium titanate coating was prepared as a comparative example and compared with Ni powder coated with barium titanate (Example 1).

[0042] The first step is to pretreat the Ni powder raw material

[0043] 2 g of Ni powder was added to a dilute sodium carbonate solution, and the solution was ultrasonically cleaned to obtain an alkaline solution containing Ni powder; the alkaline solution containing Ni powder after ultrasonic cleaning was washed with deionized water at room temperature of 25° C. to obtain Ni powder washed with deionized water;

[0044] Step 2: Prepare the liquid

[0045] At room temperature of 25°C, 2 g of pretreated Ni powder and 0.4 g of PVP dispersant were added to a water solvent, dispersed with a homogenizer for 5 min, then ultrasonically treated for 10 min, and mechanically stirred for 6 h to obtain a suspension A;

[0046] The third step is to prepare pure Ni powder by spray drying.

[0047] Pure Ni powder is prepared by spray drying equipment. The specific process steps are: set the circulating air volume (95%) of the circulating fan, the air inlet temperature (110°C), the air compressor outlet pressure (5kg), the high-pressure gas flow (6L / min), the peristaltic pump speed (30), the air inlet temperature display is the same as the set temperature display or the outlet temperature display has exceeded 90°C, and after confirming that the spray dryer system has reached the preset various indicators and is operating normally and stably, the formal liquid material (the suspension prepared in the first step) can be entered into the spray drying process. Since the spray drying process is carried out in a hot air field, the dried powder may be adsorbed on the wall of the glass instrument due to electrostatic action, which is normal. Ni metal powder can be obtained after spray drying.

[0048] 2. Results Analysis and Characterization

[0049] As attached Figure 1 As shown in the figure, it is the XRD diffraction pattern of pure Ni powder, which has a high degree of crystallinity. Figure 6 As shown, it is the volume shrinkage curve of pure Ni powder. During the sintering process in the range of 50 to 1200°C, the final volume shrinkage is 24.76%, and the volume shrinkage change is significantly greater than that of BaTiO3 powder.

[0050] Example 1

[0051] The first step is to pretreat the Ni powder raw material

[0052] 2 g of Ni powder was added to a dilute sodium carbonate solution, and the solution was ultrasonically cleaned to obtain an alkaline solution containing Ni powder; the alkaline solution containing Ni powder after ultrasonic cleaning was washed with deionized water at room temperature of 25° C. to obtain Ni powder washed with deionized water;

[0053] Step 2: Prepare the liquid

[0054] At room temperature, 2 g of pretreated Ni powder and 0.4 g of PVP dispersant were added to an aqueous solvent, dispersed with a homogenizer for 5 minutes, and then ultrasonically treated for 10 minutes to obtain a suspension A; at room temperature, 0.855 g of barium hydroxide was dissolved in an aqueous solution, ultrasonically dispersed and vibrated for 10 minutes, and then 0.49 g of titanic acid was added, dispersed with a homogenizer for 5 minutes, and then ultrasonically dispersed and vibrated for 10 minutes to obtain a mixed solution B; at room temperature, colloid B was added to suspension A, mechanically stirred for 6 hours, and fully mixed to obtain a suspension C for spray drying.

[0055] Furthermore, in the suspension A, the mass ratio of Ni powder to dispersant is 5:1, and the concentration of Ni powder is 4 g / 1L.

[0056] Furthermore, in the suspension B, the molar ratio of titanic acid to barium hydroxide is 1:1.

[0057] Furthermore, the suspension A is 500 ml, and the suspension B is 50 ml.

[0058] The third step is to prepare the Ni-based composite intermediate by spray drying;

[0059] The spray drying equipment is used to prepare the Ni-based composite intermediate with the suspension prepared in the first step as the formal liquid material. The specific process steps are: setting the circulating air volume (95%) of the circulating fan, the air inlet temperature (110°C), the air outlet pressure (5kg), the high-pressure gas flow (6L / min), the peristaltic pump speed (30), when the air inlet temperature display is the same as the set temperature display or the outlet temperature display has exceeded 90°C, and after confirming that the spray drying equipment has reached various preset indicators and is operating normally and stably, the spray drying process of the formal liquid material (the suspension prepared in the first step) can be entered.

[0060] Step 4: Prepare barium titanate coated Ni powder by heating under N2 atmosphere

[0061] The filtered powder was placed in a tubular furnace, the equipment was vacuumed, and heated and decomposed at 500°C for 4 hours. After the tubular furnace was cooled to room temperature, the final powder product was collected.

[0062] 2. Results Analysis and Characterization

[0063] As attached Figure 1 As shown, it is the XRD diffraction pattern of Ni@BaTiO3 powder. According to the standard PDF#79-2263 card, obvious Ni phase and cubic phase BaTIO3 diffraction peaks appear.

[0064] As attached Figure 2 The figure shows the EDS element distribution of Ni@BaTiO3 powder particles, in which the Ni element is concentrated in a spherical area, that is, the Ni particle is the core, and the elements such as Ba, Ti, and O are evenly distributed on its surface. This core / shell structure particle has good sphericity. Combined with the XRD analysis results, it can be concluded that its shell is BaTiO3.

[0065] As attached Figure 3 As shown, it is the EDS line scan element distribution of Ni@BaTiO3 powder particles. It can be seen from the figure that the Ni element is concentrated in the middle part of the particle, and the Ba, Ti, and O elements are distributed in the edge area of ​​the particle, which is consistent with the structure with Ni as the core and BaTiO3 as the shell.

[0066] As attached Figure 4(a) shows the morphology and size distribution of Ni@BaTiO3 powder particles. It can be seen from the figure that the obtained powder particles have a spherical morphology and a certain amount of particle agglomeration.

[0067] As attached Figure 5 As shown in the volume shrinkage curve of pure Ni powder, the final volume shrinkage is 24.76% during the sintering process in the range of 50-1200°C, and the volume shrinkage change is significantly greater than the 4.2% shrinkage of BaTiO3 powder. The sintering shrinkage of Ni@BaTiO3 powder in Example 1 is greatly reduced compared with that in Comparative Example 1, which is 10.36%, and its anti-sintering performance is significantly improved. This shows that the present invention significantly improves the performance of metal powder to a certain extent.

[0068] Example 2

[0069] Preparation process

[0070] The first step is to pretreat the Ni powder raw material

[0071] 2 g of Ni powder was added to a dilute sodium carbonate solution, and the solution was ultrasonically cleaned to obtain an alkaline solution containing Ni powder; the alkaline solution containing Ni powder after ultrasonic cleaning was washed with deionized water at room temperature of 25° C. to obtain Ni powder washed with deionized water;

[0072] Step 2: Prepare the liquid

[0073] At room temperature, 2 g of pretreated Ni powder and 1 g of citric acid dispersant were added to an ethanol solvent, dispersed with a homogenizer for 7 minutes, and then ultrasonically treated for 20 minutes to obtain a suspension A; at room temperature, 3.42 g of barium hydroxide was dissolved in an aqueous solution, ultrasonically dispersed and vibrated for 20 minutes, and then 0.98 g of titanic acid was added, dispersed with a homogenizer for 7 minutes, and then ultrasonically dispersed and vibrated for 20 minutes to obtain a suspension B; at room temperature, the suspension B was added to the suspension A, mechanically stirred for 9 hours, and fully mixed to obtain a suspension C for spray drying.

[0074] Furthermore, in the suspension A, the mass ratio of Ni powder to dispersant is 2:1, and the concentration of Ni powder is 4 g / 1L.

[0075] Furthermore, in the suspension B, the molar ratio of titanic acid to barium hydroxide is 1:2.

[0076] Furthermore, the suspension A is 500 ml, and the suspension B is 50 ml.

[0077] The third step is to prepare the Ni-based composite intermediate by spray drying;

[0078] The spray drying equipment is used to prepare the Ni-based composite intermediate with the suspension prepared in the first step as the formal liquid material. The specific process steps are: setting the circulating air volume and air inlet temperature of the central fan of the spray drying equipment, the outlet pressure of the air compressor, the high-pressure gas flow rate, and the speed of the peristaltic pump. When the air inlet temperature display is the same as the set temperature display or the outlet temperature display exceeds 90°C, and it is determined that the spray drying equipment has reached various preset indicators and is operating normally and stably, the spray drying process of the formal liquid material (the suspension prepared in the first step) can be entered. After spray drying, the Ni-based composite intermediate can be obtained.

[0079] Step 4: Prepare barium titanate coated Ni powder by heating under N2 atmosphere

[0080] The filtered powder was placed in a tubular furnace, the tubular furnace was evacuated, and heated and decomposed at 600°C for 5 hours. After the tubular furnace was cooled to room temperature, the final powder product was collected.

[0081] 2. Results Analysis and Characterization

[0082] As attached Figure 1 As shown, it is the XRD diffraction spectrum of Ni@BaTiO3 powder. According to the standard PDF#79-2263 card, obvious Ni phase and cubic phase BaTIO3 diffraction peaks appear. It can be seen from the figure that the metal powder obtained by the present invention has good crystallinity.

[0083] As attached Figure 4 (b) shows the morphology and size distribution of Ni@BaTiO3 powder particles. It can be seen from the figure that the particles obtained by the method of the present invention have good sphericity and dispersibility.

[0084] As attached Figure 6 As shown in the volume shrinkage curve of pure Ni powder, the final volume shrinkage is 24.76% during the sintering process in the range of 50-1200°C, and the volume shrinkage change is significantly greater than the shrinkage of BaTiO3 powder of 4.2%. The sintering shrinkage of Ni@BaTiO3 powder in Example 2 is very close to that of BaTiO3 powder, which is only 5.96%. Compared with Comparative Example 1, this shows that the present invention significantly improves the performance of metal powder to a certain extent.

[0085] Example 3

[0086] 1. Preparation process

[0087] The first step is to pretreat the Ni powder raw material

[0088] 2 g of Ni powder was added to a dilute sodium carbonate solution, and the solution was ultrasonically cleaned to obtain an alkaline solution containing Ni powder; the alkaline solution containing Ni powder after ultrasonic cleaning was washed with deionized water at room temperature of 25° C. to obtain Ni powder washed with deionized water;

[0089] 2. The second step is to prepare the liquid

[0090] At room temperature, 2 g of pretreated Ni powder and 2 g of polyethylene glycol dispersant were added to an aqueous solvent, dispersed with a homogenizer for 10 minutes, and then ultrasonically treated for 30 minutes to obtain a suspension A; at room temperature, 6.84 g of barium hydroxide was dissolved in an aqueous solution, ultrasonically dispersed and vibrated for 30 minutes, and then 0.98 g of titanic acid was added, dispersed with a homogenizer for 7 minutes, and then ultrasonically dispersed and vibrated for 20 minutes to obtain a mixed solution B; at room temperature, colloid B was added to suspension A, mechanically stirred for 9 hours, and fully mixed to obtain a suspension C for spray drying.

[0091] Furthermore, in the suspension A, the mass ratio of Ni powder to dispersant is 1:1, and the concentration of Ni powder is 4 g / 1L.

[0092] Furthermore, in the suspension B, the molar ratio of titanic acid to barium hydroxide is 1:4.

[0093] Furthermore, the suspension A is 500 ml, and the suspension B is 50 ml.

[0094] The third step is to prepare the Ni-based composite intermediate by spray drying;

[0095] The spray drying equipment is used to prepare the Ni-based composite intermediate with the suspension prepared in the first step as the formal liquid material. The specific process steps are: setting the circulating air volume and air inlet temperature of the central fan of the spray drying equipment, the outlet pressure of the air compressor, the high-pressure gas flow rate, and the speed of the peristaltic pump. When the air inlet temperature display is the same as the set temperature display or the outlet temperature display exceeds 90°C, and it is determined that the spray drying equipment has reached various preset indicators and is operating normally and stably, the spray drying process of the formal liquid material (the suspension prepared in the first step) can be entered. After spray drying, the Ni-based composite intermediate can be obtained.

[0096] Step 4: Prepare barium titanate coated Ni powder by heating under N2 atmosphere

[0097] The filtered powder was placed in a tubular furnace, the equipment was vacuumed, and heated and decomposed at 700°C for 6 hours. After the tubular furnace was cooled to room temperature, the final powder product was collected.

[0098] 3. Results Analysis and Characterization

[0099] As attached Figure 1 As shown, it is the XRD diffraction spectrum of Ni@BaTiO3 powder. According to the standard PDF#79-2263 card, obvious Ni phase and cubic phase BaTIO3 diffraction peaks appear. It can be seen from the figure that the metal powder obtained by the present invention has good crystallinity.

[0100] As attached Figure 4 (c) shows the morphology and size distribution of Ni@BaTiO3 powder particles. It can be seen from the figure that the particle size distribution is uniform.

[0101] As attached Figure 7 As shown in the volume shrinkage curve of pure Ni powder, the final volume shrinkage is 24.76% during the sintering process in the range of 50-1200°C, and the shrinkage of BaTiO3 powder is 4.2%. The sintering shrinkage of Ni@BaTiO3 powder in Example 3 is reduced to a certain extent, which is 14.88%. Compared with Comparative Example 1, this shows that the present invention significantly improves the performance of metal powder to a certain extent.

[0102] Example 4

[0103] 1. Preparation process

[0104] The first step is to pretreat the Ni powder raw material

[0105] 2 g of Ni powder was added to a dilute sodium carbonate solution, and the solution was ultrasonically cleaned to obtain an alkaline solution containing Ni powder; the alkaline solution containing Ni powder after ultrasonic cleaning was washed with deionized water at room temperature of 25° C. to obtain Ni powder washed with deionized water;

[0106] Step 2: Prepare the liquid

[0107] At room temperature, 2 g of pretreated Ni powder and 1 g of citric acid dispersant were added to a solvent of water and ethanol (volume ratio 1:1), dispersed with a homogenizer for 7 minutes, and then ultrasonically treated for 20 minutes to obtain a suspension A; at room temperature, 1.71 g of barium hydroxide was dissolved in an aqueous solution, ultrasonically dispersed and vibrated for 20 minutes, and then 0.98 g of titanic acid was added, dispersed with a homogenizer for 7 minutes, and then ultrasonically dispersed and vibrated for 20 minutes to obtain a mixed solution B; at room temperature, colloid B was added to suspension A, mechanically stirred for 9 hours, and fully mixed to obtain a suspension C for spray drying.

[0108] Furthermore, in the suspension A, the mass ratio of Ni powder to dispersant is 2:1, and the concentration of Ni powder is 4 g / 1L.

[0109] Furthermore, in the suspension B, the molar ratio of titanic acid to barium hydroxide is 1:1.

[0110] Furthermore, the suspension A is 500 ml, and the suspension B is 50 ml.

[0111] The third step is to prepare the Ni-based composite intermediate by spray drying;

[0112] The spray drying equipment is used to prepare the Ni-based composite intermediate with the suspension prepared in the first step as the formal liquid material. The specific process steps are: setting the circulating air volume and air inlet temperature of the central fan of the spray drying equipment, the outlet pressure of the air compressor, the high-pressure gas flow rate, and the speed of the peristaltic pump. When the air inlet temperature display is the same as the set temperature display or the outlet temperature display exceeds 90°C, and it is determined that the spray drying equipment has reached various preset indicators and is operating normally and stably, the spray drying process of the formal liquid material (the suspension prepared in the first step) can be entered.

[0113] Step 4: Prepare barium titanate coated Ni powder by heating under N2 atmosphere

[0114] The filtered powder was placed in a tubular furnace, the equipment was vacuumed, and heated and decomposed at 600°C for 5 hours. After the tubular furnace was cooled to room temperature, the final powder product was collected.

[0115] 2. Results Analysis and Characterization

[0116] As attached Figure 4 (b) shows the morphology and size distribution of Ni@BaTiO3 powder particles. It can be seen from the figure that the particles have good sphericity and some fine particles are agglomerated.

[0117] As attached Figure 8 As shown in the volume shrinkage curve of pure Ni powder, the final volume shrinkage is 24.76% during the sintering process in the range of 50 to 1200°C, and the volume shrinkage change is significantly greater than the shrinkage of BaTiO3 powder of 4.2%. Compared with Comparative Example 1, the shrinkage of Example 4 at around 1200°C is 20.46%, which indicates that the present invention significantly improves the performance of metal powder to a certain extent.

[0118] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A method for synthesizing barium titanate coated Ni inner electrode material assisted by spray drying technology, characterized in that: The method described herein firstly uses titanic acid and barium hydroxide as raw materials, mixes them with nano- and submicron Ni powders to prepare a mixed solution; secondly, a Ni-based composite intermediate is synthesized by a spray drying method based on the obtained mixed solution; finally, barium titanate-coated Ni powder is formed after sintering in a tubular furnace (N2 atmosphere).

2. The method for synthesizing barium titanate-coated Ni inner electrode material assisted by spray drying technology according to claim 1, characterized in that: The method described is specific The following steps are involved: The first step is to pretreat the Ni powder raw material; Adding Ni powder to a dilute sodium carbonate solution and performing ultrasonic cleaning on the solution to obtain an alkaline solution containing Ni powder; cleaning the alkaline solution containing Ni powder after ultrasonic cleaning to obtain Ni powder after cleaning with deionized water; The second step is to prepare the feed liquid; The Ni powder and dispersant after the pretreatment in the first step are added to the solvent, and ultrasonic treatment is performed after dispersion to obtain suspension A, in which the mass ratio of Ni powder to dispersant is 5:(1-3); at room temperature, barium hydroxide is dissolved in an aqueous solution, and titanic acid is added after ultrasonic dispersion and vibration, and ultrasonic dispersion and vibration are performed again after dispersion to obtain suspension B, in which the molar ratio of titanic acid to barium hydroxide is 1:1-1:4; at room temperature, suspension B is added to suspension A, mechanical stirring is performed for 6-12 hours, and sufficient mixing is performed to obtain suspension C for spray drying; The third step is to prepare the Ni-based composite intermediate by spray drying; A spray drying device is used to prepare a Ni-based composite intermediate using the suspension C prepared in the second step as a formal liquid material; Step 4: preparing barium titanate coated Ni powder by heating under N2 atmosphere; The powder collected after spray drying is placed in a tubular furnace, the tubular furnace is vacuumed, and a heating decomposition treatment is performed at a certain temperature. After the tubular furnace is cooled to room temperature, the final powder product is collected.

3. The method for spray drying assisted synthesis of barium titanate coated Ni inner electrode material according to claim 2, characterized in that: In the first step, the Ni powder is nanometer or submicron level or a mixed powder of nanometer and submicron level.

4. The method for synthesizing barium titanate coated Ni inner electrode material assisted by spray drying technology according to claim 2, characterized in that: The solvent in the suspension A includes one or more of deionized water, ethanol, ethylene glycol or other organic solvents; the dispersant includes one or more of polyvinyl pyrrolidone PVP, polyethylene glycol, citric acid and sodium citrate.

5. The method for spray drying assisted synthesis of barium titanate coated Ni inner electrode material according to claim 4, characterized in that: The suspension A is preferably deionized water.

6. The method for synthesizing barium titanate-coated Ni inner electrode material assisted by spray drying technology according to claim 2, characterized in that: The concentration of Ni powder in the suspension A is 4 g / 1L; The volume ratio of the suspension A to the suspension B is 10:1; The dispersion time in the suspension A is 5 to 10 minutes, and the ultrasonic treatment time is 10 to 30 minutes; The ultrasonic dispersion vibration time in the suspension B is 10 to 30 minutes, the dispersion time after adding metatitanic acid is 10 to 30 minutes, and the ultrasonic dispersion vibration time is again 10 to 30 minutes.

7. The method for spray drying assisted synthesis of barium titanate coated Ni inner electrode material according to claim 2, characterized in that: The specific process of the third step is: setting the circulating air volume and air inlet temperature of the central fan of the spray drying equipment, the outlet pressure of the air compressor, the high-pressure gas flow rate, and the peristaltic pump speed; when the air inlet temperature display is the same as the set temperature display or the outlet temperature display has exceeded 90°C, and it is determined that the spray drying equipment has reached various preset indicators and is operating normally and stably, the formal liquid spray drying process is entered, and the Ni-based composite material intermediate can be obtained after spray drying.

8. The method for spray drying assisted synthesis of barium titanate coated Ni inner electrode material according to claim 2, characterized in that: In the fourth step, the temperature of the thermal decomposition treatment is 500-700° C. and the time is 4-6 hours.

9. A spray drying technology-assisted synthesis of barium titanate-coated Ni particle material prepared by the method according to any one of claims 1 to 8, characterized in that: The barium titanate coated Ni inner electrode material is a Ni@BaTiO3 spherical particle with a core-shell structure, which is a barium titanate coated modified Ni powder material obtained by coating Ni powder. The particles have a core / shell microstructure, the shell layer is a barium titanate coating layer, the thickness of which is in the range of 10 to 15 nm, and the particle size of the particles is between 100 and 150 nm.

10. The spray drying technology-assisted synthesis of barium titanate-coated Ni particle material according to claim 9, characterized in that: The core / shell microstructure, particle size and distribution of the particles are regulated by controlling the ratio of barium hydroxide and metatitanic acid, the type and addition amount of the dispersant and parameters related to the spray drying process.

Citation Information

Patent Citations

  • Barium titanate coated nanometer nickel powder for inner electrode of MLCC (Multilayer Ceramic Capacitor) and preparation method thereof

    CN103508736A

  • Amorphous silicon oxide coated modified nickel powder electrode material for ceramic capacitor and preparation method of amorphous silicon oxide coated modified nickel powder electrode material

    CN117583598A

  • Core / shell type silver-coated copper powder synthesized on basis of atomization drying and heat treatment processes and preparation method of core / shell type silver-coated copper powder

    CN118832160A

  • Method for synthesizing amorphous silicon oxide coated nickel powder with assistance of chemical precipitation and atomization granulation

    CN118926523A

  • Method for coating nickel powder with barium titanate

    CN119501080A

Cited By

  • Preparation method of spherical nanometer barium titanate coated nickel powder

    CN122625641A